Study guides

☆☆

Q: 4xy plus 1 equals 3y-7x solve for y?

Write your answer...

Submit

Still have questions?

Related questions

2y + 2xy' + 4y + 4xy' = 0 6y + 6xy' = 0 y' = -y/x

It is 4xy.

It is 4xy.

4xy + x3y + yx2 + yx + 3yx = x3y + x2y + 8xy = (xy)(x2y + x + 8)

It is 4xy.

4xy - 2y(x + 4) = 4xy - 2xy - 8y = 2xy - 8y = 2y(x - 4)

(x + 3)(x + 4y)

the difference between 2x2 +4xy-3 and x2-2xy-4 is?

If by "What is the answer to", you mean "How do you factor", then we can solve it as follows: x2 + 13xy + 36y2 = x2 + 4xy + 9xy + 36y2 = x(x + 4y) + 9y(x + 4y) = (x + 9y)(x + 4y)

It is 4xy.

3x2y - 4xy + 4x

-1

People also asked